The structure of the adverbs in Japanese language. - Nurelova., A. M. (Journal of Oriental Studies, 2016)
This article discusses the structure of the adverbs, word formation adverbs in Japanese language. And also it is conducted a comparative analysis with adverbs in Kazakh language.